Eosinophilic Arteritis Related Spontaneous Coronary Artery Dissection a Case Report - Çengel, Gülden; Olgun, Esra Gürlek; Kureş, Semih Alper; Uysal, Cafer; Çakmak, Mehmet Ali; Can, İsmail Özgür (The Bulletin of Legal Medicine, 2015)
Spontaneous dissection of coronary arteries is accepted as one of the rare reasons of myocardial infarction. Spontaneous non-traumatic coronary artery dissection occurs rarely. Eosinophilic periarteritis of coronary artery may cause coronary artery dissection. Coronary eosinophilic periarteritis is put forward as predisposing factor of intimai impairment and dissection. In the literature; 1/3 of women with eosinophilic periarteritis is pregnant or in postpartum stage. In our case, 35 aged postpartum woman, who was deteriorated at home is brought hospital as dead. In the histopathological examination of tissue samples taken by the autopsy, made in The Council of Forensic Medicine, dissection in the left descending branch of coronary artery related to eosinophilic periarteritis and thyroiditis in the thyroid tissue samples is observed. In the literature, there is a few death case, related eosinophilic periarteritis with, autoimmune thyroiditis. It is found important because of that it i s one of the pathologies, which must come to mind firstly in postpartum period women deaths.Keywords: Postpartum, Arteritis, Eosinophilic, Coronary, Dissection.
Keywords: postpartum; arteritis; eosinophilic; coronary; dissection